TiO2 / WxV1-xO2 / ZrO2 multilayer film intelligent energy-saving coating system and preparation method thereof
By adopting the TiO2/WxV1-xO2/ZrO2 multi-layer film structure in the VO2 smart window coating, the problem of excessive phase transition temperature and difficult to take into account both the VO2 coating, and the consideration of low phase transition temperature and high optical performance is achieved.
Patent Information
- Application Number
- CN202411871390.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
In applications, VO2 smart window coatings have problems such as excessive phase transition temperature and difficulty in obtaining both visible light transmittance and high solar light modulation capabilities.
The TiO2/WxV1-xO2/ZrO2 multi-layer film structure is adopted, and the phase transition temperature is reduced by W doping VO2 film, TiO2 is selected as the seed layer to improve crystallization quality, and ZrO2 is used as the anti-reverse layer to regulate optical performance, achieving low Tc, high Tlum and high △Tsol.
The phase transition temperature of the TiO2/WxV1-xO2/ZrO2 multilayer film system was successfully reduced to 37°C, while maintaining the visible light transmittance above 40% and the solar light modulation capacity reached 11.9%, meeting the optical performance requirements of smart windows.
Smart Images

Figure CN119710548A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor optoelectronic materials, and in particular to a TiO2 / W x V 1-x O2 / ZrO2 multilayer thin film intelligent energy-saving coating and preparation method thereof. Background Art
[0002] The global warming problem caused by the greenhouse effect is one of the biggest challenges facing mankind in this century, and has brought many problems to human society, such as extreme weather and ecosystem damage. Since these problems are closely related to energy, and uncontrolled energy consumption will aggravate the greenhouse effect, the use of energy-saving windows in buildings has become one of the primary standards for modern architecture. Smart energy-saving windows are windows that can automatically adjust infrared transmittance according to changes in indoor and outdoor temperatures; in winter, when the indoor temperature is low, smart windows automatically adjust to increase their own solar transmittance, allowing more sunlight to enter the room, thereby increasing the indoor temperature; in summer, when the indoor temperature is high, smart windows automatically adjust to reduce their own transmittance to infrared band light (the main source of thermal effect), thereby reducing the indoor temperature.
[0003] As the temperature changes, VO2 changes at the phase transition temperature (T c ) will undergo a metal-semiconductor transition (MST) and its transmittance to the near-infrared region will change dramatically. c Below (68°C), VO2 behaves as a semiconductor phase with high transmittance to near-infrared light. When the phase transition temperature exceeds T c , its semiconductor phase (M-VO2) transforms to the metallic phase (R-VO2), showing high reflectivity to near-infrared light. Therefore, VO2 is considered to be the best candidate material for thermochromic smart window coatings.
[0004] In order to realize the practical application of VO2 smart energy-saving windows, VO2 smart window coatings need to meet the following conditions at the same time:
[0005] 1) Its T c It should be close to room temperature (30°C); 2) Visible light transmittance (T lum ) is not less than 40% to meet daily lighting needs; 3) The modulation capacity of sunlight △T sol However, the current VO2 smart window coating has T c (68℃) is too high and the visible light transmittance (T lum ) and high solar modulation capability (△T sol ) is a problem that is difficult to have both.
[0006] Based on the above technical status, the present invention application is specially proposed. Summary of the invention
[0007] Aiming at the insufficient performance of VO2 in smart window applications, the present invention provides a TiO2 / W x V 1- x O2 / ZrO2 multilayer thin film intelligent energy-saving coating system and its preparation method. By doping VO2 thin film with W to reduce the MST phase transition temperature, the appropriate W doping content can make TiO2 / W x V 1-x The phase transition temperature of the O2 / ZrO2 multilayer film intelligent energy-saving coating system is reduced to 37°C; TiO2 is selected as the seed layer to increase the W x V 1-x O2 thin film crystal quality; Use ZrO2 as an anti-reflection layer to regulate the optical properties of multilayer thin film systems (T lum , △T sol ), by adjusting the process parameters, TiO2 / W x V 1-x The solar light modulation capability of the O2 / ZrO2 multi-layer thin film intelligent energy-saving coating system reaches 11.9%, while the visible light transmittance remains above 40%.
[0008] In order to achieve the above-mentioned optical performance requirements of the smart window coating, the technical solution adopted by the present invention is as follows:
[0009] A TiO2 / W x V 1-x O2 / ZrO2 multilayer film intelligent energy-saving coating system, characterized in that the multilayer film chemical formula is TiO2 / W x V 1-x O2 / ZrO2, wherein: 0.01≤x≤0.03; the TiO2 seed layer crystal phase is anatase phase, W x V 1- x O2 is an intelligent energy-saving functional layer that generates MST with temperature, and the ZrO2 anti-reflection layer is an amorphous film.
[0010] The present invention reduces the phase transition temperature of VO2-based intelligent energy-saving coating by doping VO2 with metal W element; selects TiO2 as a seed layer to improve the crystallization quality of W-doped VO2 film, and selects ZrO2 as an anti-reflection layer to improve the optical properties of W-doped VO2 film. The present invention prepares TiO2 / W by introducing TiO2 seed layer and ZrO2 anti-reflection layer. x V 1-x O2 / ZrO2 multilayer film system, further control the multilayer film process parameters to prepare low T c , high T lum and high △T sol VO2-based intelligent energy-saving coating.
[0011] The second object of the present invention is to provide the above-mentioned TiO2 / W x V 1-x A method for preparing an O2 / ZrO2 multilayer thin film system, the method specifically comprising the following steps:
[0012] (1) Selecting a suitable quartz glass substrate and performing cleaning and drying pretreatment on the substrate;
[0013] (2) A TiO2 seed layer is prepared on the surface of the pretreated quartz glass substrate, and then a W x V 1-x O2 smart film layer, finally in W x V 1-x A ZrO2 anti-reflection layer is prepared on the O2 smart film layer.
[0014] Wherein, the thickness of the TiO2 seed layer mentioned in step (2) is 40-60nm, W x V 1-x The thickness of O2 is 60-80nm, and the thickness of ZrO2 anti-reflection layer is 120-230nm.
[0015] In addition, in step (2), TiO2 / W x V 1-x The preparation of O2 / ZrO2 multilayer films can be achieved not only by pulsed laser deposition, but also by magnetron sputtering or electron beam evaporation.
[0016] Furthermore, for TiO2 / W x V 1-x For the preparation of O2 / ZrO2 multilayer films, pulsed laser deposition is considered as the preferred method, and its specific process is as follows:
[0017] The pulsed laser deposition method was used. First, TiO2 ceramics were used as the target material, the substrate temperature was controlled at 400°C, the pulsed laser energy was 200-600mJ / Pulse, and the deposition oxygen pressure was 0-10Pa. A TiO2 seed layer was deposited on the surface of a clean and dry quartz glass substrate. Then, W-doped V2O5 ceramics were used as the target material, the substrate temperature was controlled at 600°C, the pulsed laser energy was 200-600mJ / Pulse, and the deposition oxygen pressure was 0-10Pa. x V 1-x O2 film; finally, ZrO2 ceramics were used as the target, the substrate temperature was controlled to be room temperature, the pulse laser energy was 200-600mJ / Pulse, the deposition oxygen pressure was 0-10Pa, and the W x V 1-x A ZrO2 anti-reflection layer is deposited on the surface of the O2 film.
[0018] Preferably, in the above technical solution, the deposition time is 15-120 minutes.
[0019] Optionally, the W x V 1-x The preparation method of O2 ceramics includes:
[0020] WO3 and V2O5 are mixed evenly and ground after adding water to obtain a mixed powder; the mixed powder is then placed in a vacuum drying oven at 80-120°C for 10-12 hours, then crushed and pressed into discs; the discs are then placed in a vacuum tube furnace and fired at 300-800°C for 1-6 hours to obtain W-doped V2O5 ceramics. The same TiO2 and ZrO2 ceramic targets are also prepared using the above steps, and optionally, the sintering temperature is 600-1200°C.
[0021] Optional, 0.01≤x≤0.03.
[0022] Compared with the prior art, the present invention provides a TiO2 / W x V 1-x The O2 / ZrO2 multilayer thin film intelligent energy-saving system and its preparation method have shown the following significant advantages and beneficial effects:
[0023] (1) TiO2 / W provided by the present invention x V 1-x The O2 / ZrO2 smart coating has metal-semiconductor transition characteristics, and its metal-insulator transition (i.e., MST phase transition) temperature is between 37°C and 74°C.
[0024] (2) The multilayer film system prepared by the present invention has a light transmittance of 40.3%-40.6% in the visible light wavelength range, and a modulation capability of 11.3%-11.9% for infrared light in the wavelength range of 300-2500nm.
[0025] (3) TiO2 / W provided by the present invention x V 1-x The O2 / ZrO2 smart coating can be prepared by pulsed laser deposition, magnetron sputtering, electron beam evaporation and other technical means. The equipment required is simple and cheap, and the operation process is simple and easy. The ZrO2 anti-reflection layer of the present invention can be used for W x V 1-x The O2 layer plays a protective role and prolongs its lifespan. In addition, each layer of the film has low requirements for the growth environment and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The TiO2 / W grown on a quartz glass substrate of the present invention xV 1-x Schematic diagram of the structure of O2 / ZrO2 multilayer film;
[0027] Figure 2 The TiO2 / W prepared in Example 1 of the present invention 0.01 V 0.99 XRD patterns of O2 / ZrO2 multilayer films;
[0028] Figure 3 The TiO2 / W prepared in Example 1 of the present invention 0.01 V 0.99 Transmission spectrum of O2 / ZrO2 multilayer film;
[0029] Figure 4 The TiO2 / W prepared in Example 1 of the present invention 0.01 V 0.99 The transmittance of O2 / ZrO2 multilayer film at 2500nm wavelength varies with temperature;
[0030] Figure 5 The TiO2 / W prepared in Example 1 of the present invention 0.01 V 0.99 Differential curve of transmittance of O2 / ZrO2 multilayer film versus temperature;
[0031] Figure 6 The TiO2 / W prepared in Example 1 of the present invention 0.01 V 0.99 Transmission spectra of O2 / ZrO2 multilayer films after being placed in the atmosphere for 6 months;
[0032] Figure 7 The TiO2 / W prepared in Example 2 of the present invention 0.03 V 0.97 XRD patterns of O2 / ZrO2 multilayer films;
[0033] Figure 8 The TiO2 / W prepared in Example 1 of the present invention 0.03 V 0.97 Transmission spectrum of O2 / ZrO2 multilayer film;
[0034] Fig. 9 The TiO2 / W prepared in Example 1 of the present invention 0.03 V 0.97 The transmittance of O2 / ZrO2 multilayer film varies with temperature at 2500nm wavelength;
[0035] Fig.10 The TiO2 / W prepared in Example 1 of the present invention 0.03 V 0.97Differential curve of transmittance of O2 / ZrO2 multilayer film versus temperature;
[0036] Fig.11 The TiO2 / W prepared in Example 2 of the present invention 0.03 V 0.97 Transmission spectra of O2 / ZrO2 multilayer films placed in the atmosphere for 6 months;
[0037] Fig.12 is the XRD spectrum of the VO2 thin film prepared in Comparative Example 1 of the present invention;
[0038] Fig.13 is the transmission spectrum of the VO2 thin film prepared in Comparative Example 1 of the present invention;
[0039] Fig.14 The transmittance of the VO2 thin film prepared in Comparative Example 1 of the present invention varies with temperature at a wavelength of 2500nm;
[0040] Fig.15 It is a temperature differential processing diagram of the transmittance-temperature curve of the VO2 film prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The details of the present invention will be further explained through implementation cases below. This implementation case is based on the technical framework of the present invention and aims to highlight the innovativeness of the present invention through detailed implementation steps and specific operation processes. However, it should be noted that the protection scope of the present invention is not limited to the implementation cases described below. According to the implementation mode provided by the present invention, any variants and improvements that do not deviate from the core idea of the present invention and do not involve additional creative efforts should be deemed to be within the scope of protection of the present invention.
[0042] It should be noted that the substrates used in the present invention are all quartz glass, the main component of which is SiO2. The specification of the quartz glass in the present invention is 10×10 mm. 2 .
[0043] The present invention grows a (101) crystal plane oriented anatase phase TiO2 seed layer on the pretreated quartz glass substrate, and then prepares a (011) crystal plane oriented W on the surface of the TiO2 seed layer. x V 1-x O2 film, and finally W x V 1-x The amorphous ZrO2 anti-reflection layer is prepared on the O2 film.
[0044] Example 1
[0045] The present application provides a TiO2 / W 0.01 V0.99 O2 / ZrO2 multilayer film, characterized in that the multilayer film comprises:
[0046] Glass substrate;
[0047] A TiO2 seed layer, located on the surface of the substrate;
[0048] W 0.01 V 0.99 An O2 functional layer is located on a surface of the TiO2 seed layer away from the glass substrate;
[0049] The ZrO2 anti-reflection layer is located on the W 0.01 V 0.99 The O2 functional layer is away from the surface of one side of the glass substrate.
[0050] The above-mentioned TiO2 / W 0.01 V 0.99 The preparation method of O2 / ZrO2 multilayer film comprises the following steps:
[0051] S1. In order to prepare the ablation target, firstly, WO3 and V2O5 powders with a molar ratio of WO3:V2O5 of 1:99.5 are fully mixed, and then an appropriate amount of water is added for ball milling for 6 hours. Then, the mixed powder is placed in a vacuum drying oven and dried at 100°C for 10 hours. After drying, the powder is crushed and pressed into a disc. Finally, the disc is placed in a vacuum tube furnace and sintered at 620°C for 6 hours to obtain the desired W-doped V2O5 ceramic target. Similarly, the above steps are also used for TiO2 and ZrO2 ceramic targets, and their sintering temperatures are 1300°C and 1200°C, respectively, and the sintering time is 12 hours.
[0052] S2. Take quartz glass as the substrate, use acetone, ethanol and deionized water as cleaning agents, and ultrasonically clean the substrate in turn, with each cleaning time of 15 minutes. After cleaning, quickly blow dry the surface of the substrate with nitrogen, and then immediately place it in the vacuum chamber of the pulsed laser deposition system. Next, use pulsed laser deposition technology to deposit thin films using ceramic targets corresponding to each layer of material prepared in step S1. During this process, adjust the distance between the target stage and the sample stage to 55mm, the laser pulse energy to 260mJ / pulse, the pulse laser frequency to 5Hz, and the rotation speeds of the sample stage and target stage to 10r / min and 5r / min, respectively. In particular, when depositing the TiO2 layer, the substrate temperature is 400°C and the oxygen pressure in the vacuum chamber is 1.0Pa; when depositing W 0.01 V 0.99 When depositing the O2 layer, the substrate temperature is 750°C and the oxygen pressure in the vacuum chamber is 1.3 Pa. When depositing the ZrO2 layer, the substrate temperature is room temperature and the oxygen pressure in the vacuum chamber is 1.0 Pa.
[0053] Structure and performance test:
[0054] The TiO2 / W prepared in this example 0.01 V 0.99 The full XRD spectrum of O2 / ZrO2 thin film is as follows Figure 2 The peak at 2θ = 25.3° is the diffraction peak of the TiO2 anatase phase (101) crystal plane; the peak at 2θ = 28.1° is the W 0.01 V 0.99 O2 monoclinic phase (011) crystal plane diffraction peak; no diffraction peak of ZrO2 appears in the XRD spectrum, indicating that the prepared ZrO2 film is amorphous.
[0055] Figure 3 The TiO2 / W prepared in this example 0.01 V 0.99 The transmission spectrum test results of O2 / ZrO2 multilayer film. The results show that the TiO2 / W prepared in this embodiment 0.01 V 0.99 The transmittance of the O2 / ZrO2 multilayer film in the visible light band is 40.6% at room temperature. 0.01 V 0.99 The modulation rate of O2 / ZrO2 film to sunlight is 11.3%, indicating that it has a strong ability to regulate sunlight.
[0056] Figure 4 The TiO2 / W prepared in this example 0.01 V 0.99 The curve of the transmittance of O2 / ZrO2 film at 2500nm wavelength versus temperature. The experimental results show that for infrared light with a wavelength of 2500nm, the difference between the high and low temperature transmittance of the sample is 48%, indicating that the sample has a good infrared switching effect. The differential treatment of the curve of the transmittance of the sample versus temperature can determine that the phase transition temperature of the sample is 56℃( Figure 5 ).
[0057] Figure 6 The TiO2 / W prepared in this example 0.01 V 0.99 The transmission spectrum of the O2 / ZrO2 film was obtained after being placed in the atmosphere for 6 months. The results show that compared with 6 months ago, the transmittance of the sample in the wavelength range of 300-2500nm has no significant change, indicating that the TiO2 / W prepared in this example 0.01 V 0.99 O2 / ZrO2 film has very good stability and meets the application requirements of smart windows.
[0058] Example 2
[0059] The present application provides a TiO2 / W 0.03 V 0.97 O2 / ZrO2 multilayer film system, characterized in that the multilayer film comprises:
[0060] Glass substrate;
[0061] A TiO2 seed layer, located on the surface of the substrate;
[0062] W 0.03 V 0.97 An O2 functional layer is located on a surface of the TiO2 seed layer away from the glass substrate;
[0063] The ZrO2 anti-reflection layer is located on the W 0.03 V 0.97 The O2 functional layer is away from the surface of one side of the glass substrate.
[0064] The above-mentioned TiO2 / W 0.03 V 0.97 The preparation method of O2 / ZrO2 multilayer film comprises the following steps:
[0065] S1. In order to prepare the ablation target, firstly, WO3 and V2O5 powders with a molar ratio of WO3:V2O5 of 1:49.5 are fully mixed, and then an appropriate amount of water is added for ball milling for 6 hours. Then, the mixed powder is placed in a vacuum drying oven and dried at 100°C for 10 hours. After drying, the powder is crushed and pressed into a disc. Finally, the disc is placed in a vacuum tube furnace and sintered at 620°C for 6 hours to obtain the desired W-doped V2O5 ceramic target. Similarly, the above steps are also used for TiO2 and ZrO2 ceramic targets, and their sintering temperatures are 1300°C and 1200°C, respectively, and the sintering time is 12 hours.
[0066] S2. Take quartz glass as the substrate, use acetone, ethanol and deionized water as cleaning agents, and ultrasonically clean the substrate in turn, with each cleaning time of 15 minutes. After cleaning, quickly blow dry the surface of the substrate with nitrogen, and then immediately place it in the vacuum chamber of the pulsed laser deposition system. Next, use pulsed laser deposition technology to deposit thin films using ceramic targets corresponding to each layer of material prepared in step S1. During this process, adjust the distance between the target stage and the sample stage to 55mm, the laser pulse energy to 260mJ / pulse, the pulse laser frequency to 5Hz, and the rotation speeds of the sample stage and target stage to 10r / min and 5r / min, respectively. In particular, when depositing the TiO2 layer, the substrate temperature is 400°C and the oxygen pressure in the vacuum chamber is 1.0Pa; when depositing W 0.03 V 0.97When depositing the O2 layer, the substrate temperature is 750°C and the oxygen pressure in the vacuum chamber is 1.3 Pa; when depositing the ZrO2 layer, the substrate temperature is room temperature and the oxygen pressure in the vacuum chamber is 1.0 Pa.
[0067] Structure and performance test:
[0068] The TiO2 / W prepared in this example 0.03 V 0.97 The full XRD spectrum of O2 / ZrO2 thin film is as follows Figure 7 The peak at 2θ = 25.3° is the diffraction peak of the TiO2 anatase phase (101) crystal plane; the peak at 2θ = 28.1° is the W 0.03 V 0.97 O2 monoclinic phase (011) crystal plane diffraction peak; no diffraction peak of ZrO2 appears in the XRD spectrum, indicating that the prepared ZrO2 film is amorphous.
[0069] Figure 8 The TiO2 / W prepared in this example 0.03 V 0.97 The transmission spectrum test results of O2 / ZrO2 multilayer film. The results show that the TiO2 / W prepared in this embodiment 0.03 V 0.97 The transmittance of the O2 / ZrO2 film in the visible light band is 40.6% at room temperature. 0.03 V 0.97 The modulation rate of O2 / ZrO2 film to sunlight is 11.9%, indicating that it has a strong ability to regulate sunlight.
[0070] Fig. 9 The TiO2 / W prepared in this example 0.03 V 0.97 The curve of the transmittance of O2 / ZrO2 film at 2500nm wavelength changing with temperature. The experimental results show that for infrared light with a wavelength of 2500nm, the difference between the high and low temperature transmittance of the sample is 41%, indicating that the sample has a good infrared switching effect. The curve of the transmittance of the sample changing with temperature is then differentiated to determine that the phase transition temperature of the sample is 37℃( Fig.10 ).
[0071] Fig.11 The TiO2 / W prepared in this example 0.03 V 0.97 The transmission spectrum of the O2 / ZrO2 film was obtained after being placed in the atmosphere for 6 months. The results show that compared with 6 months ago, the transmittance of the sample in the wavelength range of 300-2500nm has no significant change, indicating that the TiO2 / W prepared in this example 0.03 V 0.97O2 / ZrO2 film has very good stability and meets the application requirements of smart windows.
[0072] Comparative Example 1
[0073] This comparative example is a VO2 semiconductor thin film material deposited on a quartz glass substrate, which is prepared by the following method:
[0074] S1. To prepare the ablation target, V2O5 was ball-milled with water for 6 hours. Then, the powder was placed in a vacuum drying oven and dried at 100°C for 10 hours. After drying, the powder was crushed and pressed into a disc. Finally, the disc was placed in a vacuum tube furnace for sintering at 620°C for 6 hours to obtain the desired V2O5 ceramic target.
[0075] S2, using quartz glass as the substrate, using acetone, ethanol and deionized water as cleaning agents, ultrasonically cleaning the substrate in turn, each cleaning time is 15 minutes. After cleaning, the substrate surface is quickly blown dry with nitrogen, and then immediately placed in the vacuum chamber of the pulsed laser deposition system; using the pulsed laser deposition method, using the V2O5 ceramic target prepared in step S1, set the distance between the target stage and the sample stage to 55mm, the laser pulse energy to 260mJ / pulse, the pulse laser frequency to 5Hz, the rotation speeds of the sample stage and the target stage to 10r / min and 5r / min respectively, the substrate temperature to 750℃, and the vacuum chamber oxygen pressure to 1Pa.
[0076] Structure and performance test:
[0077] The XRD spectrum of the VO2 thin film prepared in this comparative example is as follows Fig.12 As shown, the peak at 2θ=28.1° is the diffraction peak of the VO2 monoclinic phase (011) crystal plane, and there are no other impurity peaks in the spectrum.
[0078] Fig.13 The transmission spectrum of the VO2 film prepared in Example 1 is shown in Table 1. The results show that the transmittance of the VO2 film prepared in Example 1 in the visible light band is 32.6% at room temperature, and its modulation rate to sunlight is 10.8%, which is significantly lower than that of the TiO2 / W in Examples 1 and 2. x V 1-x O2 / ZrO2 multilayer films.
[0079] Fig.14 The curve of the transmittance of the VO2 film prepared in Example 1 at 2500nm wavelength varies with temperature. The experimental results show that for infrared light with a wavelength of 2500nm, the difference between the high and low temperature transmittance of the sample is 56%, indicating that the sample has a good infrared switching effect. The curve of the transmittance of the sample varying with temperature is then differentiated to determine that the phase transition temperature of the sample is 69℃( Fig.15 )。
Claims
1. A TiO2 / W x V 1-x O2 / ZrO2 multilayer thin film system, characterized in that: The multilayer film comprises: a glass substrate; A TiO2 seed layer, located on the surface of the substrate; W x V 1-x An O2 functional layer is located on a surface of the TiO2 seed layer away from the glass substrate; The ZrO2 anti-reflection layer is located on the W x V 1-x The O2 functional layer is away from the surface of the glass substrate; Among them: 0.01≤x≤0.
03.
2. As claimed in claim 1, the seed layer is an anatase phase TiO2 thin film with a (101) crystal plane orientation, and its growth temperature is 400°C.
3. As claimed in claim 1 x V 1-x The crystal plane orientation of the O2 film is (011), the phase structure is monoclinic, and its growth temperature is 600℃.
4. As claimed in claim 1, the anti-reflection layer ZrO2 is an amorphous thin film, and its growth temperature is room temperature.
5. A TiO2 / W as claimed in claims 1 to 6 x V 1-x A method for preparing an O2 / ZrO2 multilayer film, the method specifically comprising the following steps: (1) Selecting a suitable substrate and pre-treating the substrate by cleaning and drying; (2) Preparation of TiO2 / W on the surface of the pretreated substrate x V 1-x O2 / ZrO2 multilayer films; in: The substrate in step (1) is quartz glass; the TiO2 / W x V 1-x O2 / ZrO2 multilayer films can be prepared by magnetron sputtering, electron beam evaporation, pulsed laser deposition and other methods. The specific process is as follows: The TiO2 seed layer was deposited on the surface of a clean and dry quartz glass substrate by pulsed laser deposition method with TiO2 ceramic as the target, substrate temperature of 400°C, pulse laser energy of 200-600mJ / Pulse, and deposition oxygen pressure of 0-10Pa. Then, W-doped V2O5 ceramic was used as the target, substrate temperature of 600°C, pulse laser energy of 200-600mJ / Pulse, and deposition oxygen pressure of 0-10Pa were controlled to deposit W on the surface of the TiO2 seed layer. x V 1-x O2 thin film; ZrO2 ceramics were used as the target material, the substrate temperature was controlled to be room temperature, the pulse laser energy was 200-600mJ / Pulse, the deposition oxygen pressure was 0-10Pa, and the W x V 1-x A ZrO2 anti-reflection layer is deposited on the surface of the O2 film.
6. TiO2 / W according to claim 5 x V 1-x The preparation method of O2 / ZrO2 multilayer thin film material is characterized by: The thickness of the TiO2 seed layer in step (2) is 40-60 nm. x V 1-x The thickness of the O2 film is 50-80nm, and the thickness of the anti-reflection layer ZrO2 film is 120-220nm.
7. TiO2 / W according to claim 5 x V 1-x The preparation method of O2 / ZrO2 multilayer thin film material is characterized by: The deposition time of each layer of material is 10-120 minutes.
8. A TiO2 / W x V 1-x Application of O2 / ZrO2 multilayer thin film system in intelligent energy-saving coatings.